Vacío legal en el Código Laboral por la no regulación del acoso laboral - Chuquimarca., Blanca Rosa (2015)
Labor relations between the employer and the worker or employer or employee permanently involve complex situations and circumstances arising from the activities carried out under the contract of employment; contractual arrangements and the same scheme of work in Ecuador merits as a policy priority review to incorporate figures and institutions that fit the current employer labor relation and covering gaps towards the effective protection of the rights and principles labor rights. Workplace harassment is any behavior that constitutes assault or repeated harassment, exercised by the employer or by one or more workers against another and other workers, by any means and that results for those affected or her impairment abuse or humiliation, or dawn or harm their employment status or employment opportunities. Workplace bullying is a form of torture that pollutes the right of people to work with responsibility, efficiency in harmony, freely and with great spirit of entrepreneurship, the harassed person generates phobia to work, loss of competitiveness, selflessness, depression , anxiety, anguish and the company an economic lag or poor performance of professionalism. Although harassment may seem an action brought from the upper to the feeder, can occur in any direction: higher, lower to upper and peer. It depends on the personality of the harassed, the harasser, their number of employees and the circumstances in workplaces. Therefore I suggest you add in the Labour Code Art. 173 after the numeral 3 other numeral related to bullying workers, working for sitting backed legal standard if a given moment are in this situation and can exercise their rights